PERANCANGAN MEJA DAPUR ERGONOMIS PADA MASYARAKAT DESA - SURYANI SURYANI; BASUKI ARIANTO; WT. BHIRAWA (JURNAL TEKNIK INDUSTRI, 2018)
Cikuya village is a village located at the foot of Mount Lagadar, 10 km from the Pasteur toll Jakarta direction. Nearly 60% or 378 female residents of RW 01, Kampung Cikuya work as a housewife, with the level of education completed primary school as much as 241 out of 637 women, doubles as a food vendor who spends most of his time in the kitchen. After switching from kerosene to gas, residents of Kampung Cikuya create own kitchen table made of wood or a wall. The design of the kitchen table that they make are usually not fit to the user's body, can be too low or too high. It can interfere with the comfort and safety of its users who are women. Therefore, it is necessary to design the kitchen table in accordance with the principles of ergonomics. The term ergonomics means designing a safe, convenient, and efficient, healthy, besides, Science ergonomics is also associated with the physical characteristics of humans.On this research, writer do direct measurements on 32 women aged 18-59 years. Anthropometric data measured is consist of : elbow height, fore arm's reach, thick chest, and arm span. Data processing use statistical science to find the average (mean) and also standard deviation. After that, writer test the data. Data testing consist of : the adequacy of the data, the data uniformity test, normality test data and determine the value of the test persentil.Untuk data using SPSS software.The results is elbow height average RW 01 is 92.03 cm. Thick average chest 25.31 cm, fore arm reach 70.65 cm and 154.4 cm hand span. Using a 5% percentile obtained size kitchen tablet, writer can get table height 88 cm, width 55 cm table and table length 143 cm. On this research writer have 2 alternative design. On alternative design 1, the table is made with storage by using as a framework meranti wood, wood overlaid with multiplex and HPI (high pressure laminate), as the top surface layer using aluminum. Alternative design 1 cost of Rp. 1.609 million. While the second alternative, the design of the table without a storage. Alternative design 2 made of with meranti wood frame, multiplex surface coatings and aluminum. Alternative design 2 cost is Rp.626.000Keywords: Design kitchen table, Ergonomics, Cikuya village